2015
DOI: 10.1097/ccm.0000000000001261
|View full text |Cite
|
Sign up to set email alerts
|

The Centers for Disease Control and Prevention’s New Definitions for Complications of Mechanical Ventilation Shift the Focus of Quality Surveillance and Predict Clinical Outcomes in a PICU

Abstract: The definitions for the various ventilator-associated conditions are good predictors of outcomes in children and adults and are amenable to automated surveillance. Based on the study findings, we suggest consideration for shifting the focus of surveillance for ventilator-associated events from only pneumonia to a broader range of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 11 publications
4
44
3
Order By: Relevance
“…By conducting a retrospective case control study, Lewis et al found that mandatory modes of ventilation and fluid status are risks for VAC while initiating benzodiazepines prior to intubation, opioid exposures and paralytic medications are risks for IVAC (16). Another retrospective cohort study demonstrated immunocompromised status, tracheostomy dependence and chronic respiratory disease are risk factors for VAE but this research was completed in a pediatric ICU (17). According to the results of our study, eight factors were screened from 17 candidates and were verified as the risks for VAE.…”
Section: Discussionmentioning
confidence: 99%
“…By conducting a retrospective case control study, Lewis et al found that mandatory modes of ventilation and fluid status are risks for VAC while initiating benzodiazepines prior to intubation, opioid exposures and paralytic medications are risks for IVAC (16). Another retrospective cohort study demonstrated immunocompromised status, tracheostomy dependence and chronic respiratory disease are risk factors for VAE but this research was completed in a pediatric ICU (17). According to the results of our study, eight factors were screened from 17 candidates and were verified as the risks for VAE.…”
Section: Discussionmentioning
confidence: 99%
“…VAP is the second most common type of health care associated infection and is associated with increased prolonged mechanical ventilator days and PICU length of stay. 38,39 In adult populations NSI as an intervention has been shown to reduce the risk of developing microbiologically proven VAP by 54% (95% CI 18%-74%). 40 However, in paediatrics, small underpowered paediatric studies have been unable to detect a significant association between NSI and the incidence of VAP.…”
Section: Saementioning
confidence: 99%
“…The potential preventative strategies for VAE in adults are breathing trials and paired daily spontaneous wakening, early exercise and mobility, low tidal volume ventilation, fluid management and conservative blood transfusion thresholds (Klompas, 2015). One study has applied this surveillance definition to paediatrics (Phongjitsiri et al, 2015). The authors found that VAE was most commonly due to atelectasis, sepsis, ARDS and shock.…”
Section: Mechanical Ventilation and Vap And Vaementioning
confidence: 99%
“…The lack of updated paediatric specific VAP prevention strategies in PICUs suggests there are grounds for further research to inform paediatric evidence-based VAP preventative strategies. Scant evidence exists around preventative strategies specifically for VAE in PICU patients (Cocoros, Priebe, Gray, et al, 2017;Phongjitsiri et al, 2015).…”
Section: Mechanical Ventilation and Vap And Vaementioning
confidence: 99%
See 1 more Smart Citation